2023
DOI: 10.3390/ijms24065547
|View full text |Cite
|
Sign up to set email alerts
|

GmGSTU23 Encoding a Tau Class Glutathione S-Transferase Protein Enhances the Salt Tolerance of Soybean (Glycine max L.)

Abstract: Salt stress has a detrimental impact on crop yield, quality, and profitability. The tau-like glutathione transferases (GSTs) represent a significant group of enzymes that play a crucial role in plant stress responses, including salt stress. In this study, we identified a tau-like glutathione transferase family gene from soybean named GmGSTU23. Expression pattern analysis revealed that GmGSTU23 was predominantly expressed in the roots and flowers and exhibited a concentration–time-specific pattern in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Plant glutathione S-transferases (GSTs) are ubiquitous and multifunctional enzymes, which are induced by various abiotic and biotic stimuli (Cao et al, 2022;Gullner et al, 2018;Li et al, 2023). Some GSTs consist of the ROS-producing and -scavenging network genes which are essential for ROS homeostasis (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Plant glutathione S-transferases (GSTs) are ubiquitous and multifunctional enzymes, which are induced by various abiotic and biotic stimuli (Cao et al, 2022;Gullner et al, 2018;Li et al, 2023). Some GSTs consist of the ROS-producing and -scavenging network genes which are essential for ROS homeostasis (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 74 DEGs in the glutathione metabolic pathway were significantly enriched, and of these 36 DEGs were glutathione S-transferase (GST) genes. In soybeans, overexpression of GmGSTU23 was associated with significantly higher GST activity, GR activity and GSH content of transgenic plants relative to wild type plants under salt stress, indicating that enhanced glutathione transferase activity could mediate ROS clearance and glutathione content 57 . Here we found that LOC_Os06g12290 expression was significantly higher than that of other GST genes, reflecting its importance in responses to salt stress.…”
Section: Discussionmentioning
confidence: 97%
“…The TaZFP reported in this study is a novel gene associated with RSIR-RV, and the other gene, TaGST , is related to RSIR-RtL and RSIR-RsA. Overexpressing GST in cotton or soybean improves their salt tolerance [ 42 , 43 , 44 ]. In addition, GST is involved in scavenging ROS induced by salt stress in cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the salt-stress response in Arabidopsis , kinase proteins play a crucial role in ion transport and in signal transduction [ 46 , 47 ]. Some genes referred to transcription and translation, such as the 60S ribosomal protein L5 (RPL-5), ATP synthase subunit b (ATP5H), and RNA-binding protein (RBP), which are related to salt tolerance in rice or cotton [ 42 , 43 , 44 ], and some genes referred to the metabolic processes in response to salt stress [ 48 , 49 ], such as the aminotransferase-related protein gene and ketol-acid reductoisomerase NADP(+) (KARI). In addition, two ERF genes, TraesCS6A02G301900 and TraesCS6B02G331000 , were also induced.…”
Section: Discussionmentioning
confidence: 99%